The SAGE encyclopedia of quality and the service economy - Dahlgaard-Park, Su Mi; Sage eBooks (Thousand Oaks, California : SAGE Publications, 2015)
Services now constitute the largest share of GDP in most countries and provide the major source of employment in both developed and developing countries. The emergence of the service economy strengthened the importance of quality issues, which no longer are associated only with manufacturing industries but are increasingly applied in all service sectors. Thus, quality and services have emerged in parallel as closely interrelated fields.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 12, 2015).
Keywords: Service industries -- Quality control -- Encyclopedias; Electronic books